Social Fiqhi Analysis of Career Women in Fulfilling Family Support in the Bugis Community in Ganra District, Soppeng Regency - Yuliana Dewi Amriana; Rahmawati; Saidah; Rusdaya Basri; Aris (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research discusses career women and fulfilling their family's livelihood in the Bugis community in Ganra District, Soppeng Regency through social fiqhi analysis. This is based on the dynamics of life development, namely the involvement of women in the world of work with the nickname of career women to participate in providing for the family. The main problems are: 1) What are the factors that encourage women in Bugis community families in Ganra District to become career women? 2) What is the social fiqhi analysis of career women in fulfilling their family's livelihood in the Bugis community in Ganra District?. The author conducted research using a descriptive qualitative method approach; the data sources in this research are housewives who work as honorary workers, ulama, the Head of Ganra District, and the community in Ganra District (primary data) and documents on the condition of the population in Ganra District (secondary data); The research instrument is the researcher himself and is assisted through data collection tools, namely observation sheets, interview guides, digital cameras and tape recorders; data collection techniques are observation, interviews, and documentation; and testing the validity of research data, namely credibility, transferability, dependability, and confirmability. The main problem solving process in this research uses grand theory, namely the theory of social jurisprudence and the theory of the role of women. The results of this research show that 1) The involvement of women from Bugis community families in Ganra District in the world of work is influenced by various factors, namely: economic factors, lack of husband's income to meet all household needs. Educational factor, a form of women's self-actualization regarding the education they have received. Technological developments, availability of jobs that suit your skills. Financial independence, reducing dependence on husband. 2) In Bugis families, women who are married and want to work outside the home must first obtain permission from their husbands. This is in line with the principles of social fiqhi, namely legal contextualization, maslahah, dynamic/adaptive, social role in law, and social justice which shows that men and women have the same opportunities to improve their abilities in the world of work. Women who have received permission to work outside the home are obliged to maintain a balance between their rights and obligations as housewives and career women. However, in the position of fulfilling family support, the obligation is the man's duty as a husband. Meanwhile, women's work is seen as a form of financial support for themselves and their families.